1995
DOI: 10.1023/a:1016246028338
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results are consistent with previous knowledge of the release mechanisms of these formulations. ER adinazolam mesylate and ER alprazolam 0.5 mg exhibit primarily a diffusion controlled release mechanism, while ER alprazolam 3 mg deviates from pure diffusional release. The limitations of the model are discussed and point to the need for continued study of the swelling kinetics of matrix ER systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(15 citation statements)
references
References 6 publications
1
14
0
Order By: Relevance
“…[1][2][3][4] This conclusion is supported by our recent study of the concentration dependence of drug diffusivity in the presence of the major components (drug, lactose, and water) in HPMC gel solution. 3 Using the Higuchi equation for soluble drugs, we demonstrated that the dependence of drug diffusivity upon the concentrations of HPMC, lactose, and drug can be correlated to the change in drug release rate as a function of formulation composition.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…[1][2][3][4] This conclusion is supported by our recent study of the concentration dependence of drug diffusivity in the presence of the major components (drug, lactose, and water) in HPMC gel solution. 3 Using the Higuchi equation for soluble drugs, we demonstrated that the dependence of drug diffusivity upon the concentrations of HPMC, lactose, and drug can be correlated to the change in drug release rate as a function of formulation composition.…”
Section: Introductionsupporting
confidence: 61%
“…This conclusion is consistent with our studies of drug diffusivity in HPMC gels. 3,4 We caution, however, that our conclusions are strictly valid for soluble drugs at moderate to low matrix loadings. For insoluble drugs or soluble drugs at very high loadings, 31 matrix dissolution determines drug release rate.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In this case, the swelling behavior of MCC allowed further penetration of the aqueous medium, resulting in rapid erosion of the polymer matrices. In addition, lactose in aqueous solution plays a role as important physical barrier, affecting the release kinetics, by reducing the tortuosity of the diffusion pattern of the drug [14]. However, if it were mixed with Methocel K15 MCR, the polymer concentration would lead the release rate of the drug.…”
Section: Effect Of Lactosementioning
confidence: 99%
“…This review also includes a discussion on Na CMC for the slow release of cardiovascular drugs. The use of HPMC as a SR system has been well documented [7][8][9][10][11][12][13][14][15][16][17][18]. Hogan [19] reviewed the use of HPMC in pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%